(untitled) (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
Human resource is a very important asset for a company. A good human resource management will result to good output for company. Employee engagement is a relatively new term in the field of human resource management. According to Tritch (2003), employees who have engagement value are those who have full and enthusiastic involvement in their work. Another view of employee engagement is proposed by Macey and Schneider (2008) which states that employee engagement does not only make employees contribute more, but also result to higher loyalty which reduces the desire to leave the company voluntarily. Thomas (2007) provides an understanding of employee engagement as a stable psychological state, the result of interaction between an individual and the environment in which the individual works. The factors or aspects that make up employee engagement, popularly developed by the Kenexa Employee Engagement Index standards (EEI), are measured based on four components: Pride, Satisfaction, Advocacy and Retention. The sample of this research is all 738 employees of PT. Taman Wisata Borobudur, Prambanan, and Ratu Boko consisting of 389 Organic Employees and 349 Cooperative Employees. This research is referred to as population research since the entire population is used as a sample of the research.